Contribution of nonlocality to surface elasticity - Li, Li (2021)
The underlying mechanisms of surface phenomena are very complex and still not entirely clear. The aim of this work attempts to reveal the important contribution of the nonlocal integral theory of elasticity to surface elasticity, which is of fundamental scientific interest. By considering a uniform and isotropic half-space medium subjected to an arbitrary uniform strain, it is shown that the bulk is homogeneous, however, the whole medium is heterogeneous due to the bond loss near the free surface. The nonlocal effect cannot be observed at all in the homogeneous bulk, but the bond loss characterized by the nonlocal integral theory can show an important contribution to the surface elasticity. This in turn allows to propose a simplified surface model to replace the complex modeling of nonlocal integral theory. The thickness of surface zone can be evaluated from the intrinsic characteristic length used in the nonlocal integral theory. According to the intrinsic correlation and using the molecular dynamics simulations, the thickness of the surface layer of silicon films is 2.6911 Å. Furthermore, with application of the simplified surface model to a thin film in tension, it has been noted that the geometric dimension of size-dependence is generally not that of traditional mechanics. For instance, in most situations, the main contribution to size-dependence has actually come from the thickness (or radius) direction of a rod-type structure, rather than its axial direction which is intuitively- and widely-used in the current practice in open literature.